A case of primary racemose hemangioma with endobronchial lesions demonstrating recurrent hemoptysis initially treated with bronchial arterial embolization. (2022) - Imai, Shun; Kasai, Hajime; Sugiura, Toshihiko; Nagata, Jun; Toyoda, Takahide; Shiohira, Shunya; Shikano, Kohei; Kawame, Chiaki; Kouchi, Yusuke; Ota, Masayuki; Abe, Mitsuhiro; Suzuki, Hidemi; et al.
Abstract: Primary racemose hemangioma of the bronchial artery (RHBA) is one of the causes of massive hemoptysis. A 72-year-old woman was admitted to our hospital with recurrent hemoptysis. Bronchoscopy showed an endobronchial lesion, and the angiography of the right bronchial arteries indicated RHBA. Bronchial arterial embolization (BAE) was performed to prevent hemoptysis. Although the endobronchial lesion shrank after the first BAE, the lesion re-increased and caused massive hemoptysis. A thoracoscopic right upper lobectomy was performed, and hemoptysis did not recur. Therefore, in cases of RHBA where there is recurrent hemoptysis and the endobronchial lesions that remain after BAE, additional treatments should be considered.